An objective neural signature of rapid perspective taking. Issue 1 (27th November 2017) - Beck, Alexy A; Rossion, Bruno; Samson, Dana
Abstract: The frequency-tagging approach has generally been confined to study low-level sensory processes and always found related activation over the occipital region. Here for the first time, we investigated with it, high-level socio-cognitive functions, i.e. the processing of what other people are looking at which is referred to as level 1 visual perspective taking (VPT). Sixteen participants were presented with visual scenes alternating at 2.5 Hz which were depicting a person and an object in a room, while recording electrophysiological brain activity. The person orientation and object position changed at every stimulus but the person in the room always faced the object, except on every fifth stimulus. We found responses in the electroencephalography (EEG) spectrum exactly at the frequency corresponding to the presentation of the scenes where the person could not see the object, i.e. 0.5 Hz. While the 2.5 Hz stimulation rate response focused on typical medial occipital sites, the specific 0.5 Hz response was found mainly over a centro-parietal region. Besides a robust group effect, these responses were significant and quantifiable for most individual participants. Overall, these observations reveal a clear measure of level 1-VPT representation, highlighting the potential of EEG frequency-tagging to capture high-level socio-cognitive functions in the brain.